A novel enucleation– exenteration approach of the equine eye via the supraorbital fossa: an experimental and clinical study in donkeys (Equus asinus) - Marzok, Mohamed; Almubarak, Adel I.; Nazih, Mohamed; Al-thnaian, Thnian A.; Alkhodair, Khalid; El-Sherif, Mohamed (Frontiers in Veterinary Science, 2024)
This study investigated the description and feasibility of a surgical procedure for enucleationexenteration of the equine eye via the supraorbital fossa. Preliminary study was performed on both eyes of four cadaveric heads of native breed donkeys (Equus asinus) to describe the surgical anatomy and demonstrate a new supraorbital enucleation surgical approach. For the clinical study, eight donkeys were admitted for unilateral enucleation. All procedures were performed in lateral recumbent position under the influence of inhalation anesthesia in combination with retrobulbar nerve block. A semi-circular incision was made in the skin and fascia of the supraorbital fossa to gain access into the orbital cavity, after which the periorbital fat was dissected and removed. Bleeding was controlled by electrocautery and large blood vessels were ligated, and the eyeball was dissected sharply and freed from its bony attachment. The procedure was successfully accomplished in all clinical cases, and no significant complications occurred during or throughout the postoperative follow-up period. The initial results suggest the feasibility and safety of the supraorbital enucleation technique described in this study for equine eye enucleation. This new technique represents a promising due to its feasibility, safety, and positive outcomes observed in both cadaveric and clinical studies.